DESIGN OF CONTAINER HANDLING BERTH STRUCTURE OF PORT IN AMBON, MALUKU - NATANIEL YUWANTO (NIM : 15514012), KEVIN
Ambon (the capital of Maluku Provence) is one of the main cities in the Eastern Indonesia development region. Judged from the aspects of development and economic growth, Ambon has great potential to be developed. Gross regional domestic product (GRDP) of Ambon in 2016 recorded 12.045 billion Rupiah. For the sake of impoving the economy of Ambon, a port is needed that can support AmbonÃ‚Â’s development. In the final project case study on the design of container handling berth structure in Ambon, it will be discussed about the structure design of the dock and trestle based on the design criteria used as structural planning requirements by considering the existing conditions at the study location. The final project includes determining the dimensions of the dock and trestle, processing environmental data, calculating the load on the dock and trestle, modeling the structure, design of reinforcement structures, and calculating the capacity of the soil. Structure designed using analysis structure software to determine the ability of the structure to deal with the working load. The results of modelling is unity check ratio (UCR), structure deflection, internal forces in beams and plate, and base reactions. Design is carried out to obtain reliable and optimal design, by doing UCR checking as reference that must be between 0.8 and 1.0. checking the ratio of reinforcement value, and checking deflection value as the serviceabilty determinat. The value has to be below the permit limit. The final result of Final Project includes dock and trestle design including the dimensions of the structure, dimensions of the dock and trestle structural elements, reinforcement details based on the acting internal forces, and the erection depth plan that is able to withstand structural reactions based on available geotechnical data.